The influence of electronic human resource management on organizational performance in the Chinese tourism industry - Jia, Jing (2024)
This study explores the interrelationship between e-recruitment, e-training, e-compensation, and organizational performance in the Chinese tourism industry. Through various statistical analyses, including Pearson correlation analysis, multiple regression analysis, and descriptive analysis, key findings have been identified.